2011
DOI: 10.1016/j.socscimed.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of migration in the development of depressive symptoms among Latino immigrant parents in the USA

Abstract: Nearly one out of every four children in the US is a child of immigrants. Yet few studies have assessed how factors at various stages of migration contribute to the development of health problems in immigrant populations. Most focus only on post-migration factors influencing health. Using data from the Latino Adolescent Migration, Health, and Adaptation Project, this study assessed the extent to which pre-migration (e.g., major life events, high poverty), migration (e.g., unsafe and stressful migration experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
166
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 51 publications
8
166
0
Order By: Relevance
“…To improve personal and family life situation/living standard, search for better life and better paying job, failure to succeed in educational endeavors, poverty of family and poor life situation, unemployment, failure to succeed in educational endeavors were additional factors. The present study finding was consistently pertinent with many previous research findings in Ethiopia such as Emebet [6], Asefach [14], Agrinet [41], ILO [21], IOM [22] and Bezabih [62].Our finding is also consistent with a number of previous studies conducted in North America [63][64][65][66], Europe [67][68][69][70][71][72] and the Middle East [73,74] among migrants and refugees from different countries who found that migration related stressors (such as being unable to get salary on time and salary denial) and preparation of the migrant beforehand (e.g. awareness about the culture, the lifestyle, food and religion of the destination country) are important predictors of depression disorder symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…To improve personal and family life situation/living standard, search for better life and better paying job, failure to succeed in educational endeavors, poverty of family and poor life situation, unemployment, failure to succeed in educational endeavors were additional factors. The present study finding was consistently pertinent with many previous research findings in Ethiopia such as Emebet [6], Asefach [14], Agrinet [41], ILO [21], IOM [22] and Bezabih [62].Our finding is also consistent with a number of previous studies conducted in North America [63][64][65][66], Europe [67][68][69][70][71][72] and the Middle East [73,74] among migrants and refugees from different countries who found that migration related stressors (such as being unable to get salary on time and salary denial) and preparation of the migrant beforehand (e.g. awareness about the culture, the lifestyle, food and religion of the destination country) are important predictors of depression disorder symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The rise of anxiety and psychological problems among immigrants in the resettlement countries, in comparison with native inhabitants, has been addressed in previous studies [19][20][21][22]. Factors that may influence immigrant's psychological well-being in resettlement countries might accord our findings be traced back to the pre-migration and migration processes.…”
Section: Discussionmentioning
confidence: 54%
“…The effect of discrimination on immigrants' mental health has been addressed in previous studies [21,29]. Immigrants' experiences of discrimination in the pre-migration stage make them more vulnerable for the same processes in the post-migration phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies continue reporting a high prevalence of depressive symptoms among Mexican immigrant women and identify additional factors that affect their mental health (Fox & Kim-Godwin, 2011;Garcini et al, 2016;Ornelas & Perreira, 2011). These include: an extended time of residence in the usa, ethnic discrimination and antiimmigrant sentiments, threats of deportation, financial insecurity, loss of connections with family and friends in their country of origin, experiences of trauma, loss and adversity, language limitations, stress due to the inability to find employment, feelings of not fitting into a new culture, lack of familiarity with new environment, conflict between traditional and new customs and values, feelings of shame, and not participating in the decision to migrate.…”
Section: Introductionmentioning
confidence: 99%